Use of Post‐Acute Facility Care in Children Hospitalized With Acute Respiratory Illness. Issue 8 (1st August 2017) - Berry, Jay G.; Wilson, Karen M.; Dumas, Helene; Simpser, Edwin; O'Brien, Jane; Whitford, Kathleen; May, Rachna; Mittal, Vineeta; Murphy, Nancy; Steinhorn, David; Agrawal, Rishi; Rehm, Kris; et al.
Abstract : BACKGROUND: Recovery from respiratory illness (RI), a common reason for hospitalization, can be protracted for some children because of high illness severity or underlying medical complexity. OBJECTIVE: We assessed which children hospitalized with RI are the most likely to use post‐acute facility care (PAC) for recovery. METHODS: Retrospective analysis of 609, 800 hospitalizations for patients in 43 US children's hospitals between 2010‐2015 for RI, identified with the Agency for Healthcare Research and Quality Clinical Classification System. Discharge to PAC was identified using Centers for Medicare & Medicaid Services Discharge Status Codes. We compared patient characteristics by PAC use with generalized estimating equations. RESULTS: There were 2660 (0.4%) RI hospitalizations resulting in PAC transfer (n = 2660, 0.4%). Discharges to PAC had greater percentages of technology assistance (83.2% vs 15.1%), neuromuscular chronic condition (57.5% vs 8.9%), and mechanical ventilation (52.7% vs 9.1%), P < 0.001 for all. The highest likelihood of PAC use occurred with ≥11 vs no chronic conditions (odds ratio [OR] 11.7 [95% CI, 8.0‐17.2]), ≥9 vs no therapeutic medication classes (OR 4.8 [95% CI, 1.8‐13.0]), and existing tracheostomy (OR 3.0, 95% confidence interval [CI], 2.6‐3.5). Median (interquartile range [IQR]) acute‐care length of stay (LOS) for children most likely to use PAC was 19 (8‐56) days; LOS remained long (median 13 [6‐41] days) for children with the same attributes (n = 9448) not transferred to PAC. CONCLUSIONS: Children with RI who are most likely to use PAC have a high prevalence of multiple chronic conditions, multiple medications, and medical technology. Future investigations should assess the supply of PAC against the demand of hospitalized children with RI who might need it.